Does artificial drawdown affect zooplankton structure in shallow lakes? A short-term study in a tropical reservoir - Portinho, Jorge Laço [UNESP]; Nogueira, Marcos Gomes [UNESP] (Springer Nature, 2017)
Water level fluctuation by artificial drawdown is one management activity that has the potential to control macrophyte growth, but there is little knowledge of how this operational procedure affects other biotic components of the ecosystem. This study investigated zooplankton dynamics in response to artificial drawdown over a short timeframe (13 days) in a Brazilian reservoir, by examining the impact on zooplankton communities in two shallow lakes (Lake Pedra Branca-LPB, and Guaritá-LG) connected to a reservoir (Salto Grande) that undergo sudden and remarkable fluctuations in their water levels. Zooplankton communities were sampled in both lakes before (pre-drawdown), during (low water), and after (post-drawdown) the artificial drawdown procedure. In LPB, drawdown resulted in an increase in zooplankton density, and temporarily changed the community in association with an increase in water conductivity and presence of non-planktonic organisms during the low water phase. In LG, drawdown had no significant effect on zooplankton community between the phases before and during the drawdown event. The results from this study suggest that artificial drawdown over a short timeframe in reservoir systems do not negatively affect the overall density, richness, and diversity of zooplankton communities in marginal shallow lakes.
Keywords: Biodiversity; Microcrustaceans; Regulated rivers; Remedial measures; Rotifers; Submerged plants